A retrospective study of the added value of parallel titers compared with serial titers. Issue 10 (4th September 2019) - Lin, Yulia; Cohen, Robert; Buckstein, Jonah; Callum, Jeannie; Lieberman, Lani
Abstract : BACKGROUND: Prenatal antibody titers for alloimmunized patients are subject to multiple sources of variation. A parallel titer on the previous sample at the same time as the current sample is recommended. The purpose of this study was to determine the added value of parallel titers. STUDY DESIGN AND METHODS: This is a retrospective study of samples from consecutive prenatal patients with at least two prenatal antibody titers performed in the same pregnancy at a single institution between October 2010 and March 2017. Prenatal titers were performed using gel technology. Data were collected to determine the sensitivity and specificity of a clinically significant increase (twofold or greater) in serial titers compared with the gold standard of using parallel titers. RESULTS: There were 155 serial prenatal titers performed in 59 alloimmunized pregnant women. Nineteen samples (12%) had a serial titer increase of twofold or greater with eight false positive samples (increase less than twofold when using parallel titers). Thirty‐six samples (23%) had a serial titer increase of onefold with two false negative samples (increase of twofold or greater using parallel titers). One hundred samples (65%) had no increase (or a decrease) in serial titer with none having an increase of twofold or greater using parallel titers. The sensitivity of a twofold or greater increase in serial titers was 84.6% (95% CI 55‐98%) and the specificity was 94.4% (95% CI 89‐98%) when compared with parallel titers. CONCLUSION: This study questions the value of parallel titers on every prenatal titer performed. When no increase in serial titers was observed, parallel titers added no new information.